Studi Histopatologi Ren Tikus Putih (Rattus Norvegicus L.) Diabetes Setelah Pemberian Cuka dari Kulit Nanas (Ananas Comosus (L.) Mer.) - Tazkia Annisa; Agung Janika Sitasiwi; Sri Isdadiyanto; Siti Nur Jannah (Jurnal Sain Veteriner, 2021)
Diabetes mellitus is a metabolic disease that occurs due to impaired insulin secretion caused by progressive damage to beta cells. Pineapple skin vinegar contained acetic acid and antioxidants which have the potential to help repaired the structure of the nephron ren and other organs affected by diabetes. The purpose of this study was to examined the effectiveness of pineapple skin vinegar on improved the histological structure of diabetic rats ( Rattus norvegicus L.). This study based on changed in the structure of the nephron in samples of normal and alloxan-induced mice pre-treatmented and post-treatmented. Twenty-four rats were divided into 6 groups, named normal control, positive control (diabetes + 0.4 mL apple vinegar), negative control (diabetes + water), dose test groups 1, 2, and 3 (pineapple vinegar 0.2 mL; 0.4 mL; 0.8 mL). Statistical analysis test used ANOVA was followed by Duncan test. The conclusion of this research, the pineapple skin vinegar showed the ability to repair the histopathological structure of white rats damaged by diabetes. The optimum dose needed was 0.8 mL to improved the histological structure of the nephron, as indicated by the glomerular diameter and the distance of the Bowman's capsule space to near normal.